Le Centre d'histoire de Montréal: le passé mis au jour - Leclerc, Jean-François (Cap-aux-Diamants, 2002)
Keywords: Centre d'histoire de Montréal; Histoire; Musées

La ville au cœur de la nation : l’utilisation du passé dans l’élaboration de l’identité urbaine - Bérubé, Harold (Urban History Review / Revue d'histoire urbaine, 2002)
Keywords: Histoire

Entre praticiens et chercheurs: une histoire des psychologues au Canada, 1939-1971 - Marchand, Nicolas (Université du Québec à Montréal, 2002)
Keywords: Psychologie

Between Scientific Enquiry and the Search for a Nation: Quebec Historiography as Seen by Ronald Rudin - Fecteau, Jean-Marie (Quebec since 1800: Selected Readings, 2002)
Keywords: Histoire

Les économistes canadiens-français pendant l'entre-deux-guerres: entre la science et l'engagement - Fournier, Jonathan (Université de Sherbrooke, 2002)

H.-A. Verreau, ptre (1828-1901). Deuxième président de la Société historique de Montréal - Beaudoin, Léo (Montréal en tête, 2002)
Keywords: Chauveau, Pierre-Joseph-Olivier; Communautés religieuses; Histoire; Historiens; Société historique de Montréal; École normale Jacques-Cartier; Écoles normales

Histoire de l'Institut Bruchési et son engagement dans la lutte contre la tuberculose à Montréal (1911-1945) - Lajoie, Yves (Université de Montréal, 2002)
Keywords: Tuberculose

La médecine légale des aliénés selon Georges Villeneuve (1895-1917) - Grenier, Guy (Bulletin d'histoire politique, 2002)
Keywords: Hôpital Saint-Jean-de-Dieu; Hôpitaux psychiatriques; Médecine

L’Office provincial des recherches scientifiques et le développement de la science au Québec, 1937-1960 - Almeida, Mike (Revue d'histoire de l'Amérique française, 2002)
Keywords: Université McGill; Université de Montréal

La découverte de la "question sociale". Sociologie et mouvements d’action jeunesse canadiens-français - Warren, Jean-Philippe (Revue d'histoire de l'Amérique française, 2002)
Keywords: Association catholique de la jeunesse canadienne-française (ACJC); Jeunesse ouvrière catholique (JOC); Sociologie

Louise Lemieux Bérubé: Artist in Motion - Edeh, Rosaline U. (Université Concordia, 2002)
Keywords: Artisans; Textile

Histoire de l’Action nationale - Morin, Rosaire (L'Action nationale, 2002)
Keywords: Action nationale (L')

Québec-Montréal: l'histoire d'une classique depuis 1931 - Langlois, Gaston (G. Langlois, 2002)
Keywords: Cyclisme

Histoire du Service de santé de la ville de Montréal, 1865-1975 - Gaumer, Benoît; Desrosiers, Georges; Keel, Othmar (Culture et société, 2002)
Keywords: Fonctionnaires

Trente ans d'écrits syndicaux: contributions à l'histoire du SPUQ - Gill, Louis (Syndicat des professeurs et professeures de l'Université du Québec à Montréal, 2002)
Keywords: Enseignants; Université du Québec à Montréal

Le Domaine. Une belle histoire qui se poursuit... Les jardins du Domaine - Archambault-Malouin, Diane (Les Services du Domaine Inc, 2002)
Keywords: Domaine Saint-Sulpice; Jardins

Histoire de l'École des Hautes études commerciales de Montréal. Tome 2: 1926-1970 - Harvey, Pierre (Québec Amérique, 2002)
Keywords: École des hautes études commerciales

L'Opéra français de Montréal: l'étonnante histoire d'un succès éphémère, 1893-1896 - Barrière, Mireille (Fidès, 2002)
Keywords: Français; Opéra

La solidarité face au marché. Quelques réflexions sur l‘histoire de la mutualité au Québec - Petitclerc, Martin (Revue internationale de l'économie sociale, 2002)
Keywords: Assurance; Banques; Pauvreté; Union Saint-Joseph

Ensemble se donner une voix pour mieux être, 1977-2002: histoire du Front commun des personnes assistées sociales du Québec - Dumas, Evelyn (Front commun des personnes assistées sociales du Québec, 2002)
Keywords: Groupes populaires; Pauvreté

Les sciences infirmières: genèse d’une discipline: histoire de la Faculté des sciences infirmières de l'Université de Montréal - Cohen, Yolande; Pépin, Jacinthe; Lamontagne, Esther; Duquette, André (Presses de l'Université de Montréal, 2002)
Keywords: Infirmières; Université de Montréal

Côte Sainte-Catherine. Outre mont Royal 1694-1875 - Beauregard, Ludger (Histoire Québec, 2002)
Keywords: Côtes; Recensements; Toponymie; Voirie

Témoignages autochtones - McCaffrey, Maria T. (Continuité, 2002)
Keywords: Autochtones; Expositions; Musée McCord; Musées

Deux quotidiens se rencontrent. Le regard de l'historien - Burgess, Joanne; Lauzon, Gilles (Exposition virtuelle: Deux quotidiens se rencontrent, 2002)
Keywords: Notman, William; Photographie

Bourgoin, un pionnier de la chimie du lait - Auger, Jean-François (Cap-aux-Diamants, 2002)
Keywords: Chimie; Lait

Art, technologie et métropoles: le positionnement de Montréal comme ville d'innovation dans le secteur des nouvelles technologies - Aubé, Sylvain (Université du Québec à Montréal, 2002)

Des mémoires à «excaver» : interpréter la présence des carrières de pierre grise à Montréal - Caron, Isabelle (Journal of the Society for the Study of Architecture in Canada/Journal de la société pour l'étude de l'architecture au Canada, 2002)
Keywords: Carrière

The Defeat of George-Etienne Cartier in Montreal-East in 1872 - Young, Brian J. (The Contested Past: Reading Canada's History - Selections from the Canadian Historical Review, 2002)
Keywords: Cartier, George-Étienne

Pauvreté urbaine: la promotion de communautés viables - Séguin, Anne-Marie; Divay, Gérard (The Federal Role in Canada's Cities: Four Policy Perspectives, 2002)
Keywords: Pauvreté

Anatomically Incorrect: Bodysnatching in the Nineteenth Century - Rankin, Matthew (The Beaver, 2002)
Keywords: Criminalité; Médecine; Université McGill; Étudiants

Toronto vs Montreal: The Struggle for Financial Hegemony, 1860-1875 - Masters, D.C. (The Contested Past: Reading Canada's History - Selections from the Canadian Historical Review, 2002)
Keywords: Banques; Métropole

L’intégration scolaire des Juifs francophones et le Bulletin du Cercle juif (1954-1968) - Croteau, Jean-Philippe (Bulletin d'histoire politique, 2002)
Keywords: Francophones; Juifs

Octobre 1970: la leçon de la ﬁction - Pelletier, Jacques (Bulletin d'histoire politique, 2002)
Keywords: Crise d'octobre; Front de Libération du Québec

Des airs d’octobre - Roy, Bruno (Bulletin d'histoire politique, 2002)
Keywords: Crise d'octobre; Front de Libération du Québec; Trudeau, Pierre Elliott

Regulating Public Space in Early Nineteenth-Century Montreal: Vagrancy Laws and Gender in a Colonial Context - Poutanen, Mary Ann (Histoire sociale / Social History, 2002)
Keywords: Droit; Femmes; Itinérance

L’Église catholique du Québec et "l’épreuve" de la Révolution tranquille. Première partie: la condamnation du Frère Untel - Dassylva, Martial (Bulletin d'histoire politique, 2002)
Keywords: Langue

Notes préliminaires sur le rôle des intervenants psychiatriques et psychologiques à la Cour des jeunes délinquants à Montréal, 1912-1949 - Quevillon, Lucie (Bulletin d'histoire politique, 2002)
Keywords: Délinquance; Enfants; Psychologie; Tribunaux

Cinquante ans d’émissions religieuses à la radio québécoise (1931-1983). De l’apologétique au dialogue avec les grandes - Pagé, Pierre (Études d'histoire religieuse, 2002)
Keywords: Radio

Quand "la maison signifiait quelque chose": la famille selon l'École sociale populaire, 1918-1939 - Quesney, Chantale (Histoire sociale / Social History, 2002)
Keywords: Famille; École Sociale Populaire

Folie, internement et érosion des solidarités familiales au Québec: une analyse quantitative - Cellard, André (Bulletin d'histoire politique, 2002)
Keywords: Famille; Hôpitaux; Hôpitaux psychiatriques

Prédication et média de masse: quand le sermon devient thérapie. Portrait de l'œuvre du dominicain Marcel-Marie Desmarais - Meunier, E. -Martin (Études d'histoire religieuse, 2002)
Keywords: CKAC; Radio

L’institution ecclésiale et les structures de l’idéologie chrétienne dans les radioromans et les dramatisations historiques (1935-1975) - Legris, Renée (Études d'histoire religieuse, 2002)
Keywords: Radio; Roman

Un mouvement de droite nationale contemporain: Jeune Nation - Carel, Ivan (Bulletin d'histoire politique, 2002)

De l’École Gamelin à Rivière-des-Prairies: peut-on guérir d’un passé asilaire? - Wallot, Hubert (Bulletin d'histoire politique, 2002)
Keywords: Hôpital Rivière-des-Prairies; Hôpitaux psychiatriques

Derrière les murs de Saint-Jean-de-Dieu, fin XIXe début XXe siècles: illusion et désillusion - Thifault, Marie-Claude (Bulletin d'histoire politique, 2002)
Keywords: Hôpital Saint-Jean-de-Dieu; Hôpitaux psychiatriques

Charles-Aimé Reeves, architecte, 1872-1948 - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2002)

Les églises: lieux de culte et de culture - Vanlaethem, France (Montréal, la ville aux cent clochers. Regards des Montréalais sur leurs lieux de culte, 2002)
Keywords: Arts sacrés; Patrimoine; Sculpture; Vêtements; Églises

Protestant Restructuring in the Canadian City: Church and Mission in the Industrial Working-Class District of Griffintown, Montreal - Trigger, Rosalyn (Urban History Review / Revue d'histoire urbaine, 2002)
Keywords: Anglicans; Griffintown; Presbytériens; Protestants; Églises

La régionalisation de la production à l’Office national du film du Canada - Verronneau, Pierre (Revue d'histoire de l'Amérique française, 2002)
Keywords: Cinéma; Office national du film

The Cemetery and Cultural Memory: Montreal, 1860-1900 - Watkins, Meredith (Urban History Review / Revue d'histoire urbaine, 2002)
Keywords: Cimetières

Le déclin de la maison de fond de cour à Montréal, 1880–1920 - Carey, Luc (Urban History Review / Revue d'histoire urbaine, 2002)
Keywords: Logement

The Creative Destruction of Montreal: Street Widenings and Urban (Re) Development in the Nineteenth Century - Gilliland, Jason (Urban History Review / Revue d'histoire urbaine, 2002)
Keywords: Rues; Voirie

Déconstruire le rêve de nation: Lionel Groulx et la Révolution tranquille - Beaudreau, Sylvie (Revue d'histoire de l'Amérique française, 2002)
Keywords: Groulx, Lionel; Nationalisme

Saint-Laurent: la Main de Montréal - Anctil, Pierre (Septentrion et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2002)
Keywords: Rues; Saint-Laurent (rue)

Saint-Laurent: Montréal Main - Anctil, Pierre (Septentrion et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2002)
Keywords: Rues; Saint-Laurent (rue)

Entre la "Revanche" et la "Veillée" des berceaux: les médecins québécois francophones, la mortalité infantile et la question nationale, 1910-1940 - Baillargeon, Denyse (Revue d'histoire sur l'éducation / Historical Studies in Education, 2002)
Keywords: Enfants; Francophones; Mortalité; Médecine; Nationalisme

Designing for "the Little Convalescents" Children's Hospitals in Toronto and Montreal, 1875-2006 - Adams, Annmarie; David, Theodore (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2002)
Keywords: Enfants; Hôpitaux

Making and Breaking Bread in Jewish Montreal, 1920-1940 - Lerner, Eve (Université Concordia, 2002)
Keywords: Alimentation; Boulangerie; Juifs

L'évolution du comique de scène au Québec francophone depuis 1945 - Aird, Robert (Université du Québec à Montréal, 2002)
Keywords: Humour

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

La doctrine nazie vue par quatre journaux canadiens-français des années trente: l'Ordre, Clarté, la Nation, le Jour (1934-1939) - Patault, Annabelle (Université du Maine, 2002)
Keywords: Clarté; Jour (Le); Nation (La); Ordre (L')

La bataille du lait pur à Montréal, 1900-1926 - Colas, Valéry (Université du Québec à Montréal, 2002)
Keywords: Alimentation

La construction d'une identité étudiante montréalaise (1895-1960) - Hébert, Karine (Université du Québec à Montréal, 2002)
Keywords: Université McGill; Université de Montréal; Étudiants

Itinéraires identitaires chez des immigrants libanais de Montréal: le cas de l'identité confessionnelle - Lebnan, Karim (Université de Montréal, 2002)
Keywords: Libanais

Battles on the Homes Front: Montreal's Response to Federal Housing Initiatives, 1941-1947 - Lyons, Christopher M. (Université Concordia, 2002)
Keywords: Guerre; Logement

"Tuer le taudis qui nous tuera": crise du logement et discours sur la famille montréalaise d'après-guerre (1945-1960) - Bourbeau, Amélie (Université de Montréal, 2002)
Keywords: Logement; Pauvreté

Créer en récupérant: les enjeux de la récupération des textiles dans le design de mode québécois depuis 1980 - Simard, Isabelle (Université Laval, 2002)
Keywords: Textile; Vêtements

Vers l’avenir. Québec Women’s Politics Between 1945 and 1967: Feminist, Maternalist and Nationalist Links - Gosselin, Cheryl A. (Université de Montréal, 2002)
Keywords: Femmes; Féminisme; Nationalisme

Jacques Labrecque: trajectoire d'un "diffuseur du folklore" - Perron, Mathieu (Université Laval, 2002)
Keywords: Chanson

Commémorer la ville, une analyse comparative des célébrations du centenaire de Toronto en 1934 et du tricentenaire de Montréal en 1942 - Bérubé, Harold (Université de Montréal, 2002)
Keywords: Commémoration

Nationalisme et socialisme dans la pensée de Raoul Roy, 1935-1965 - Lapointe, Mathieu (Université de Montréal, 2002)
Keywords: Nationalisme; Socialistes

Les dynamismes organisationnels de l'institutionnalisation du sport au Québec (1900-1967) - East, Jocelyn (Université Laval, 2002)

Des intellectuels dans la cité: la ligue d'action nationale, 1933-1960 - Ryan, Pascale (Université du Québec à Montréal, 2002)
Keywords: Nationalisme

La Société Saint-Vincent de Paul de Montréal et la Fédération des Oeuvres de Charité canadiennes françaises (1933-1937) - Pincemail, Véronique (Université d'Angers, 2002)
Keywords: Fédération des œuvres de charités canadiennes-françaises (FOCCF); Saint-Vincent-de-Paul (Société)

Le Devoir et le groupe des conservateurs-nationalistes après les élections fédérales du 21 septembre 1911 - Moreau, Aurélie (Université d'Angers, 2002)
Keywords: Devoir (Le); Nationalisme; Élections

La propriété et le travail: l’enracinement des Portugais sur la Main - Andrade, Miguel Simão (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Portugais; Travail

Du rouge sur la "Main" pendant les années trente - Lévesque, Andrée (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Communistes; Quartiers; Rues; Saint-Laurent (rue); Saint-Louis

L’héritage de l’Institut du Baron Hirsch: entre la commission protestante et l’école Peretz (1880-1920) - Croteau, Jean-Philippe (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Baron de Hirsch Institute; Bureau des écoles protestantes; Juifs; Protestants

Une communauté en transition: la Petite Italie de Montréal - Del Balso, Michael (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Italiens; Petite-Italie (quartier); Quartiers

La violence dans le milieu communautaire des immigrants juifs montréalais - Robinson, Ira (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Idéologies; Juifs

Le lock-out de La Presse et l'émeute du 29 octobre 1971: un conflit d'envergure nationale - Ménard, Yves (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
Keywords: Presse (La); Émeutes

Église Orthodoxe Roumaine de l'Annonciation: 8080, rue Christophe-Colomb, Montréal (Québec) Canada: étude architecturale - Rak, Valeria-Sabina (Université Concordia, 2002)
Keywords: Roumains; Églises

The Life and Works of Dimitri Dimakopoulos Architect (1929-1995) - Marcoux, Alain (Université Concordia, 2002)

Otto Dix's Portrait of the lawyer Hugo Simons: German Art for a Canadian Museum - Cousins, Darlene Caroline (Université Concordia, 2002)
Keywords: Allemands; Peinture

La peinture murale à Montréal (1996-2001): identification et analyse d'une production culturelle - Picard, Johanne (Université de Montréal, 2002)